2019
DOI: 10.1038/s41598-019-41692-2
|View full text |Cite
|
Sign up to set email alerts
|

An integrated whole genome analysis of Mycobacterium tuberculosis reveals insights into relationship between its genome, transcriptome and methylome

Abstract: Human tuberculosis disease (TB), caused by Mycobacterium tuberculosis (Mtb), is a complex disease, with a spectrum of outcomes. Genomic, transcriptomic and methylation studies have revealed differences between Mtb lineages, likely to impact on transmission, virulence and drug resistance. However, so far no studies have integrated sequence-based genomic, transcriptomic and methylation characterisation across a common set of samples, which is critical to understand how DNA sequence and methylation affect RNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…If mntR bound to that site, it could prevent HsdM from methylating it. Meanwhile, genotyping mntR revealed that all 18 IO isolates shared the variant mntR Q131* ( Figure 5B ), a nonsense mutation found previously in IO isolates ( Gomez-Gonzalez et al, 2019 ) that truncates MntR. This truncation could explain why cobK 304 was methylated in all 18 IO isolates.…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…If mntR bound to that site, it could prevent HsdM from methylating it. Meanwhile, genotyping mntR revealed that all 18 IO isolates shared the variant mntR Q131* ( Figure 5B ), a nonsense mutation found previously in IO isolates ( Gomez-Gonzalez et al, 2019 ) that truncates MntR. This truncation could explain why cobK 304 was methylated in all 18 IO isolates.…”
Section: Resultsmentioning
confidence: 57%
“…This contrasts with the approach of prior M. tuberculosis methylome studies ( Chiner-Oms et al, 2019 ; Gomez-Gonzalez et al, 2019 ; Phelan et al, 2018 ; Shell et al, 2013 ; Zhu et al, 2016 ), which examined only the MTase motifs identified by PacBio MotifMaker ( https://github.com/PacificBiosciences/MotifMaker ). This systematic approach revealed MTase genotypes with partial function, previously mischaracterized as completely inactive ( Gomez-Gonzalez et al, 2019 ). Third, we used phylogenetic analysis to identify convergent MTase activity and heterogeneity analysis to characterize epigenomic diversity in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations